The Impact of Curriculum Changes During Each Regime on The Learning Achievement of Junior High School Students in Indonesia - Rieneke Ryke Kalalo; Moh. Nasir; Muhammad; Winda Fashiha; Rachma Putri Kasimbara (Jurnal Teknologi dan Manajemen Industri Terapan, 2025)
The Indonesian education curriculum has undergone dynamic transformations over the course of changing government regimes, from the Old Order era to the Merdeka Curriculum era. This study aims to analyze how changes in curriculum policy in each regime impacted the learning outcomes of junior high school (SMP) students. Using a descriptive qualitative method and a historical literature review, this study examines the shift in curriculum orientation from an ideological to a technocratic-competence orientation. The results of the study indicate that although curriculum changes are intended to respond to the demands of the times and globalization, "policy shock" often occurs at the grassroots level due to the lack of a transition period and adequate teacher training. Inconsistencies in implementation strategies across regimes were found to be a factor hampering the stability of student academic achievement. This study recommends that education policy be independent of short-term political interests to ensure the sustainability of the quality of national education.